The Meaning of Education From a Human Perspective: Remarks From Martha Nussbaum and Francisco Ruiz Sánchez - Di Marco, María Elisa (2020)
This paper analyzes the meaning of education from a humanist perspective developed by Martha Nussbaum and Francisco Ruiz Sánchez. There are some common points and some important differences between the proposals of these authors. In fact, in contrast to the mercantilist perspective and in favor of an anthropological position, both authors insist on the need for a more humanist education, at the measure of the human being. The hermeneutic study proposed here focuses on Nussbaum’s theory of capabilities (2007, 2012) and its links with the concept of human dignity. On the other hand, this paper presents basic concepts about the anthropological view of Ruiz Sánchez (1962a, 1962b, 1978a) such as perfectibility and fallibility, as well as other aspects that promote education as a search for human fulfillment. After carrying out this analysis, we conclude that there are many aspects in common between the two authors reviewed, but also important differences. However, both theorizations make it possible to understand education from a humanist perspective, that is, as an end in itself, because it endows the human being with dignity and fullness.